Targeting risk factors: a feasible way for prevention of vascular complications in type 2 diabetes mellitus - Irina Vladimirovna Kononenko; Olga Mikhailovna Smirnova (Сахарный диабет)
The article addresses challenges in the prevention of microvascular complications in type 2 diabetes mellitus (T2DM) and discusses necessity of multifactorial approach to management of these conditions. We present results of a large-scale ADVANCE (Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation) trial that elucidates the combined influence of antihypertensive and of intensive glucose-lowering therapy on the risk of development of micro- and macrovascular complications of T2DM